The Battle of Jericho - Draper, Sharon M. (Sharon Mills) (Draper, Sharon M. (Sharon Mills) Jericho trilogy, 2005)
When Jericho is invited to pledge for the Warriors of Distinction, he thinks his life can't get any better. As the most exclusive club in school, the Warriors give the best parties, go out with the hottest girls, and sail through their classes. And when Arielle, one of the finest girls in his class, starts coming on to him once the pledge announcements are made, Jericho is determined to do anything to become a member. But as the initiation week becomes progressively harrowing, Jericho is forced to make choices he's not entirely comfortable with. And one member seems to have i650t in for the sole female pledge in the group ... a pledge who will stop at nothing to show she can handle the pressure. But when is she being pushed too far, and when should Jericho and his friends step in and risk losing their places in the pledging process? As Jericho becomes increasingly uneasy, his cousin Joshua breezes through the initiation, never thinking of the consequences, even when the fine line between fun and games, and life and death is crossed.